2020
DOI: 10.3390/cells9092076
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Improves the Recovery of Replication-Competent Virus from Latent SIV Infected Cells

Abstract: The accurate estimation and eradication of Human Immunodeficiency Virus (HIV) viral reservoirs is limited by the incomplete reactivation of cells harboring the latent replication-competent virus. We investigated whether the in vitro and in vivo addition of retinoic acid (RA) enhances virus replication and improves the detection of latent virus. Peripheral blood mononuclear cells (PBMCs) from naive and anti-retroviral therapy (ART)-treated SIV-infected rhesus macaques (RMs) were cultured in vitro with anti-CD3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…To this end, reactivation of latent HIV/SIV by AMPK-activating agents including RA has been demonstrated [92]. This hypothesis is supported by recent studies that confirmed the ability of RA to enhance the re-activation of replication-competent viral reservoirs in peripheral rhesus macaque CD4+ T cells following activation with anti-CD3/CD28 beads to activate the T-cell receptor or PMA/ionomycin [93] (Figure 7). Likewise, Zhang et al showed that supplementation of RA during assays designed to estimate viral reservoirs showed an increase in viral replication in RA-treated versus without RA conditions [95].…”
Section: Therapeutic Potential Of Ra To Modify Hiv Pathologymentioning
confidence: 59%
See 1 more Smart Citation
“…To this end, reactivation of latent HIV/SIV by AMPK-activating agents including RA has been demonstrated [92]. This hypothesis is supported by recent studies that confirmed the ability of RA to enhance the re-activation of replication-competent viral reservoirs in peripheral rhesus macaque CD4+ T cells following activation with anti-CD3/CD28 beads to activate the T-cell receptor or PMA/ionomycin [93] (Figure 7). Likewise, Zhang et al showed that supplementation of RA during assays designed to estimate viral reservoirs showed an increase in viral replication in RA-treated versus without RA conditions [95].…”
Section: Therapeutic Potential Of Ra To Modify Hiv Pathologymentioning
confidence: 59%
“…13, x FOR PEER REVIEW 7 of 15studies that confirmed the ability of RA to enhance the re-activation of replication-competent viral reservoirs in peripheral rhesus macaque CD4+ T cells following activation with anti-CD3/CD28 beads to activate the T-cell receptor or PMA/ionomycin[93] (Figure7).…”
mentioning
confidence: 85%
“…The Tat/rev induced limiting dilution assay (TILDA) was performed as described earlier ( 85 , 86 ). In brief, enriched CD4 + T cells from frozen PBMCs or LN total cells were suspended in complete RPMI at a 2-million cells/ml concentration and then rested at 37°C and 5% CO 2 for a minimum of 2 h. After resting, cells were divided into two groups: one was stimulated with 100 ng/ml phorbol myristate acetate (PMA) and 1 μg/ml ionomycin, and the other group was left untreated as the control.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with natural, non-progressing SIV hosts, which can initiate gut healing despite chronic viremia [ 21 ]. In addition to its role in gut homeostasis, atRA, as well as synthetic analogues, have been proposed as latency-reversing agents promoting apoptosis in infected CD4+ T cells, thereby reducing the size of the viral reservoir [ 22 , 54–56 ]. However, this process may necessitate the presence of CD8+ T cells, which were experimentally depleted before infection in the present study [ 57 ].…”
Section: Discussionmentioning
confidence: 99%